An Analysis of Apology as a Politeness Strategy Expressed by the Characters in the Film â€œPrincess Diaries 2â€ (A Sociopragmatic Approach) - Christina Maya Iriana Sari (Universitas Katolik Widya Mandala Surabaya, 2015)
This research was conducted to find out the kinds of offenses motivating the characters to express apologies in the film entitled â€œPrincess Diaries 2â€, to know how the characters express their apologies and Â to reveal why the characters use the ways to express apologies as a politeness strategy. The phenomena of verbal (words or utterances), non-verbal actions supporting apologies and intonation in apologizing expressed by the characters in the film entitled â€œPrincess Diaries 2â€ are taken as the samples. There are six kinds of offences found in the film â€œPrincess Diaries 2â€ that motivate the characters to express apologies. They are deception, infringement on possession, infringements on talk, instances of inconvenience, social behavior offences, and infringement on time. The addresser performs apologies with simple or complex form. The apology strategies appearing in the data are direct apology (expression of regret and request of forgiveness), acknowledgment, expression of lack of intend, self-deficiency and expression of embarrassment, giving explanation or account, minimizing the degree of the offence, expression of Â concern to the offended, promise of forbearance and offer of repair. Furthermore, the addressers also express their apology with direct or indirect apology. Apology can also be perceived as positive politeness strategy since there is an expression of concern to the offended. Tone of voice and facial expression also support the performance of the act of apologizing expressed by the characters. Keywords: apologies, politeness, sociopragmatic